2001
DOI: 10.1023/a:1015290429403
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Carcinoma of the prostate gland is the second most common cancer among men with an age-adjusted incidence of 635 cases per 100,000 men aged 65 and older. While there are several proven methods for detecting prostate cancer, debate continues as to the best way to detect it early as well as who should receive particular screening. There are differing opinions as to proven benefit even when cancer is detected. Fortunately, newer methods continue to be developed that will hopefully reduce false positive detection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…PSA screening is, however, controversial [ 20 ]. It detects many clinically insignificant tumors which would never have caused symptoms but also sometimes misses the presence of a significant PCa [ 21 ]. The American Urological Association and US Preventive Services Task Force guidelines have suggested ages 55 to 69 to be the key age range for offering PSA to average-risk men while European urology guidelines, among others, recommend an individualised risk-adapted strategy for PSA screening in well-informed men aged over 50 years, and men aged over 45 years if they have a PCa family history [ 19 , 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…PSA screening is, however, controversial [ 20 ]. It detects many clinically insignificant tumors which would never have caused symptoms but also sometimes misses the presence of a significant PCa [ 21 ]. The American Urological Association and US Preventive Services Task Force guidelines have suggested ages 55 to 69 to be the key age range for offering PSA to average-risk men while European urology guidelines, among others, recommend an individualised risk-adapted strategy for PSA screening in well-informed men aged over 50 years, and men aged over 45 years if they have a PCa family history [ 19 , 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Men who have immediate families with PCa are about 50% more likely to develop this disease [ 51 , 52 ]. Lifestyle modifications, including smoking cessation, exercise, and weight control are preventative steps an individual can take to decrease the risk of PCa occurrence, but early screening for PCa is one of the most important steps to prevent the aggressive and advanced form of the disease [ 53 ].…”
Section: Causal Inflammatory Drivers Of Prostate Carcinogenesismentioning
confidence: 99%
“…Due to the low probability of the PSA test correctly identifying men who do not have prostate cancer (specificity), many men may be falsely identified (false positives) as possibly having prostate cancer and then subjected to unnecessary biopsies [ 77 ]. Differences in the accuracy of the PSA test are partially due to the PSA threshold used to signal a need for further testing for prostate cancer, as some thresholds may increase the detection of cancers that are unlikely to cause health concerns even if left untreated [ 78 ]. The American Cancer Society completed a series of systematic reviews and found that PSA screening for any prostate cancer with a cutoff of 4.0 ng/mL resulted in 21% of screening tests that identified prostate cancer being truly positive (sensitivity) and 91% of screening tests that did not identify prostate cancer being truly negative (specificity) [ 79 ].…”
Section: Purpose and Backgroundmentioning
confidence: 99%